1977
DOI: 10.1107/s0567740877011340
|View full text |Cite
|
Sign up to set email alerts
|

The alkaloid otosenine. Evidence of a weak –>N:...C<–O intra-annular bond

Abstract: CI9H2707N , orthorhombic, P2t2~2 a = 16.355 (7), b = 12.843 (2), c = 8.961 (1) A, Z = 4, D m = 1.34 g cm -3. The alkaloid otosenine is a pyrrolizidine derivative isolated from a senecio plant. Some features observed in the pyrrolizidine ring suggest the presence of a N... C (2.18 A) intra-annular 'one electron bond'. The macrocycle can be described in terms of pseudo twofold symmetry. Introduction.A crystal of dimensions 0.30 x 0.20 × 0.16 mm was selected for recording intensity data on a fully automated diffr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
1
0

Year Published

1979
1979
2005
2005

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 3 publications
2
1
0
Order By: Relevance
“…Therefore, it was suggested that there is a transannular interaction between the nitrogen atom and C-8 in the structure of 1 . Similar suggestions have also been made previously in view of various X-ray crystallographic studies, regarding the structure of otonecine base 1-3,5,12 and other otonecine-type PAs, including 2 , which was originally isolated from Ligularia elegans Cass …”
supporting
confidence: 79%
See 1 more Smart Citation
“…Therefore, it was suggested that there is a transannular interaction between the nitrogen atom and C-8 in the structure of 1 . Similar suggestions have also been made previously in view of various X-ray crystallographic studies, regarding the structure of otonecine base 1-3,5,12 and other otonecine-type PAs, including 2 , which was originally isolated from Ligularia elegans Cass …”
supporting
confidence: 79%
“…11 Therefore, it was suggested that there is a transannular interaction between the nitrogen atom and C-8 in the structure of 1. Similar suggestions have also been made previously in view of various X-ray crystallographic studies, regarding the structure of otonecine base [1][2][3]5,12 and other otonecine-type PAs, [18][19][20][21] including 2, which was originally isolated from Ligularia elegans Cass. 10 However, it should be noted that in all these X-ray crystallographic studies the compounds were examined as the dried crystalline form, and consequently, there has been no previous report regarding the dependency of the type of media in determining whether otonecine-type PAs exist in non-ionized or ionized forms.…”
supporting
confidence: 79%
“…Among many factors influencing the base strengths of amines, an intramolecular interaction of the lone pair of electrons at the nitrogen with a carbonyl function is well known (Perez-Salazar et al, 1977;Kaftory and Dunitz, 1975;Btirgi et al, 1973;Birnbaum, 1972;Hall, 1968). Such a type of interaction could have been expected for the acylated isoquinolylmethanols.…”
Section: Resultsmentioning
confidence: 96%